Prototipe Web KMS pada Universitas Sebagai Sarana Komunikasi Dosen dengan Kerangka “Tiwana” - Herlinda Herlinda (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
Universities need to seek the quality of lecturers. Indraprasta University is an institution with the great number resources with great potential. The lecturers have passion to keep learning, so academically skilled, dedicated and good ethical. Basically, the lecturer must master many subjects, while the subjects’ control are vary. In addition, there is no knowledge manager system yet for the lecturer, to store, discuss and utilize the joint development of knowledge related to college teaching materials. This motivated the author to build a knowledge management system to improve the competence of lecturers, by optimizing communication lines knowledge. The study was conducted using qualitative research method, case study type, with the concept of Amrit Tiwana framework model, tested with FGD and model of ISO 9126 (functionality, reliability, usability, and efficiency). Outcome is a web-based KMS prototype with features lecturer data input, subjects input, discussion forums, loading and downloading files, file searches.